2016
DOI: 10.1111/vsu.12564
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dose on Intra‐Articular Amikacin Sulfate Concentrations Following Intravenous Regional Limb Perfusion in Horses

Abstract: A 3 g amikacin dose is not justified in the majority of distal limb injuries, but should be reserved for isolates with an MIC higher than that achievable with a 2 g dose. Daily IVRLP may be necessary based on our results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 21 publications
(85 reference statements)
1
29
0
Order By: Relevance
“…17,18 Reported MIC of amikacin sulphate of commonly isolated pathogens from musculoskeletal infections ranges between 16 and 64 µg/mL. 20 Although some strains of methicillinresistant Staphylococcus aureus have a reported MIC of 500 µg/mL the median MIC for amikacin sulphate for methicillinresistant-Staphylococcus aureus in one study was reported to be 32 µg/mL. 19 Hence, the recommended C max :MIC ratio of 8:1 was reached in all horses but a 10:1 ratio for the most resistant pathogens (> 64 µg/mL) was only reached in 4/6 horses advocating for a higher dosage in horses suffering from resistant infections.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…17,18 Reported MIC of amikacin sulphate of commonly isolated pathogens from musculoskeletal infections ranges between 16 and 64 µg/mL. 20 Although some strains of methicillinresistant Staphylococcus aureus have a reported MIC of 500 µg/mL the median MIC for amikacin sulphate for methicillinresistant-Staphylococcus aureus in one study was reported to be 32 µg/mL. 19 Hence, the recommended C max :MIC ratio of 8:1 was reached in all horses but a 10:1 ratio for the most resistant pathogens (> 64 µg/mL) was only reached in 4/6 horses advocating for a higher dosage in horses suffering from resistant infections.…”
Section: Discussionmentioning
confidence: 99%
“…19 Hence, the recommended C max :MIC ratio of 8:1 was reached in all horses but a 10:1 ratio for the most resistant pathogens (> 64 µg/mL) was only reached in 4/6 horses advocating for a higher dosage in horses suffering from resistant infections. The reported dosage of amikacin sulphate in IVRLP ranges between 500 mg and 3 g. [6][7][8]10,[12][13][14][15][16]20 We choose to use 2 g in this study based on our clinical experience and previous studies that reached desirable MIC levels of synovial fluid amikacin sulphate with this dose. 6,16 To avoid potential cytotoxicity of amikacin sulphate described after intra-articular administration, the dose could be titrated according to MIC of the cultured pathogens, keeping in mind that bacteriology samples from equine orthopaedic infections frequently yield negative growth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Systemic administration is necessary to reach common sites of infection outside of the uterus, and intra‐articular administration, in the case of amikacin, allows for attainment of higher therapeutic concentrations in synovial fluid in the case of a septic joint, as compared to systemic administration. More recently, regional perfusion has proven effective in achieving high local concentrations of amikacin in the distal limb (Harvey et al, 2016; Kelmer et al, 2013; Kilcoyne et al, 2018). Advantages to intra‐articular and regional perfusion include a reduction in required doses as compared to what would be needed if administered systemically to reach these sites, thereby decreasing the potential for adverse effects.…”
Section: Introductionmentioning
confidence: 99%